2019
DOI: 10.1088/1755-1315/355/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of vertical tubular baffle heat exchanger as an internal reboiler in the distillation device

Abstract: Reboiler in the distillation device is a heat exchanger to heat or boil liquid material in the distillation column. In this research vertical tubular baffle heat exchanger was designed and used as an internal reboiler in the distillation device. The aim of the study was to observe the temperature distribution during the liquid heating process in the vertical tubular baffle heat exchanger with different dimensions. The study was conducted by designing heat exchangers (HE) with different dimensions in height, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Model validation: Validation is the procedure of verifying whether the simulating and the modeling and their related results are matching the results of the mathematical model, This comparison between the simulation and mathematical model is very important to verify these results. Table(3) shows a comparison between the Aspen Plus results obtained from the simulation and the mathematical model (design equation) we notice a great convergence between the results in the two cases, and this indicates that the simulation results are valid and reliable in design calculations, with an acceptable error margin of 7.1% for the overall heat…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Model validation: Validation is the procedure of verifying whether the simulating and the modeling and their related results are matching the results of the mathematical model, This comparison between the simulation and mathematical model is very important to verify these results. Table(3) shows a comparison between the Aspen Plus results obtained from the simulation and the mathematical model (design equation) we notice a great convergence between the results in the two cases, and this indicates that the simulation results are valid and reliable in design calculations, with an acceptable error margin of 7.1% for the overall heat…”
mentioning
confidence: 71%
“…It is important to improve and optimize the design, chemical, and physical properties used in the simulation program's approach can be calculated using statistical models. Heat exchangers with the same surface area but a different height and diameter produce a different average heat transfer coefficient [3]. a model for simulating the fluid dynamics and pillow plate thermal performance thermosiphon of reboilers' correlations for the single-phase heat transfer coefficient were used, the heat transfer coefficient with nucleate boiling was calculated [4].…”
Section: Introductionmentioning
confidence: 99%
“…The types of heat exchangers used as internal reboilers include stub in U-tube bundle reboiler (Voigt & Nj, 2013), calandria (Bhanvase et al, 2007), and vertical helical coil (Ghorbani et al, 2010). A design and test of another type of heat exchanger with different shapes and directions of fluid flow were developed by (Susmiati et al, 2019) named vertical tubular baffle. This study showed that the geometry (diameter, height, and the number of tubes) in this type of heat exchanger affects the heat transfer coefficient.…”
Section: Introductionmentioning
confidence: 99%